2019
DOI: 10.1051/metal/2018128
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of cleanliness techniques for low alloyed steel grades

Abstract: In order to find a method to characterize the inclusion distribution of high-cleanliness materials, complementary techniques were tested, such as high-frequency (80 MHz) ultrasonic testing, X-ray tomography or Extreme Value Analysis (EVA). The micro-cleanliness was also characterized by standard methods based on observations of polished surfaces by light optical or scanning electronic microscopy. The combination of all these techniques, enhanced by metiS software, allows us to determine the complete 3D distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The extent to which they are an issue in alloy use depends widely on the alloy, the application and the property concerned. Studies [2,[6][7][8][29][30][31][34][35][36][37][44][45][46]49] of the inclusion populations in remelted alloys have indicated that a general characteristic is the infrequent occurrence of large inclusions (>50 µm), but the population of small inclusions (<2 µm) may be as large as, or larger than, that in the original electrode (Figure 5).…”
Section: Inclusionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The extent to which they are an issue in alloy use depends widely on the alloy, the application and the property concerned. Studies [2,[6][7][8][29][30][31][34][35][36][37][44][45][46]49] of the inclusion populations in remelted alloys have indicated that a general characteristic is the infrequent occurrence of large inclusions (>50 µm), but the population of small inclusions (<2 µm) may be as large as, or larger than, that in the original electrode (Figure 5).…”
Section: Inclusionsmentioning
confidence: 99%
“…In almost all of the published data on inclusion populations before and after ESR, a salient feature is the absence of large inclusions in the ESR ingot [49]. It is likely that this finding does not imply a complete absence of large inclusions but instead is an indication that the population is sufficiently sparse that there is only a small probability that an inclusion might be found in a finished part located in a stress zone large enough for it to initiate a failure [49].…”
Section: Inclusionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample areas in laboratory-scale trials are usually about 100 mm 2 . According to Franceschini et al [28], an analyzed surface of 5000 mm 2 is suitable for evaluating the cleanliness for remelting processed samples, to compare with air samples where 1000 mm 2 is sufficient.…”
Section: Introductionmentioning
confidence: 99%